An Insight into Sweet Potato Weevils Management: A Review - Seow-Mun Hue; Min-Yang Low (Psyche: A Journal of Entomology)
Sweet potato is an important food crop that is grown widely in tropical and subtropical regions. Sweet potato weevil is the most disastrous pest affecting sweet potato plantations, causing millions of dollars losses annually. An effective integrated pest management (IPM) method will help to prevent economic losses, and it is crucial to understand the factors that contribute to weevil infestation and strategies that are available to overcome them. This review summarizes the (1) mechanisms of action of weevil on sweet potato and (2) contributing factors in weevil infestation, followed by (3) discussion on current IPM practices used in the different regions, including intercropping, entomopathogenic fungi and bacteria, sex pheromones, and pesticides. Lastly, it also focuses on (4) applications of advanced biotechnology and genomics strategies towards reducing weevil’s infestation in sweet potato plantation.